Sculpting Solutions: 3D-Printed Models Transform Osteotomy Planning in Monteggia Fractures - Y C Shravan; Suraj Prakash; M Mahesh; Praveen Salutagi (Journal of Orthopaedic Case Reports)
Introduction: A neglected Monteggia fracture refers to a proximal ulna fracture accompanied by a dislocated radial head that remains untreated for a duration exceeding 4 weeks following the initial injury. We present the case of a complex neglected Monteggia fracture and its unique pre-operative approach for radial head osteotomy using 3D-printed models. Case Report: An 8-year-old girl presented with a delayed diagnosis of a Monteggia fracture, which had become increasingly complex due to late intervention and prior inadequate management. We discuss the clinical presentation, radiological features, differential diagnosis, treatment options, and long-term outcomes using a unique pre-operative approach. Conclusion: 3D printing has been used around the world in orthopaedics for a myriad of fractures but we present the novel technique used in this case of a neglected Monteggia fracture which gave us access to tactile feedback of the radial head deformity with its relation to the ulnar and the capitellum which served as a blueprint in planning the osteotomy/reconstruction procedure thus improving our accuracy, efficiency intraoperatively and better overall patient outcome post-operatively.